2014
DOI: 10.1108/jaee-01-2012-0003
|View full text |Cite
|
Sign up to set email alerts
|

Professionalism, rewards, job satisfaction and organizational commitment amongst accounting professionals in Uganda

Abstract: Purpose-The purpose of this paper is to examine the extent to which the constructs of professionalism (Hall, 1968), rewards (Bartol, 1979) and job satisfaction (Stamps and Piedmonte, 1986; Hampton and Hampton, 2004) can be used as valid predictors of organizational commitment (Porter et al., 1974) in an emerging economy context. Design/methodology/approach-Using pre-existing scales for these constructs, the authors collected data from 277 ICPAU licensees' and carried out a factor analysis to examine their vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 25 publications
4
39
1
4
Order By: Relevance
“…Markovits et al [46] found the positive relation between satisfaction and commitment on in a research using Greeks as participants. The same result also found in the literatures from Azeem [47], Azeem and Akhtar [48], Irshad & Naz [49], Gunlu et al [50], Sejjaaka & Kaawaase [51], Veličković et al [52]. These researches use participants from Oman, India, Pakistan, Turkey, Uganda, and Serbia.…”
Section: Job Satisfaction and Organizational Commitmentsupporting
confidence: 74%
“…Markovits et al [46] found the positive relation between satisfaction and commitment on in a research using Greeks as participants. The same result also found in the literatures from Azeem [47], Azeem and Akhtar [48], Irshad & Naz [49], Gunlu et al [50], Sejjaaka & Kaawaase [51], Veličković et al [52]. These researches use participants from Oman, India, Pakistan, Turkey, Uganda, and Serbia.…”
Section: Job Satisfaction and Organizational Commitmentsupporting
confidence: 74%
“…A bulk of scales was adopted from related works to measure constructs. Organizational commitment was measured by organizational commitment scale developed by Meyer and Allen (1997), training was measured using a scale developed by Yahya and Goh (2002), person-organization fit was measured by a scale developed by Netemeyer et al (1997), and, finally, rewards construct was measured by a scale adopted from Sejjaaka and Kaawaase (2014). The results pointed out that all HR practices examined (training, person-organization fit, and rewards) were significantly and positively associated with organizational commitment.…”
Section: Introductionmentioning
confidence: 91%
“…All answers of scales were scored using five-point Likert scale, where 1 represents completely agree and 5 ISSN 1941-899X 2015 www.macrothink.org/jmr 226 represents completely disagree. The rewards construct was measured by a scale adopted from Sejjaaka and Kaawaase (2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have widely discussed the organizational commitment of professional jobs, particularly of accountants (e.g., Lander, Koene, & Linssen, 2013;Singh & Gupta, 2015;Chong & Monroe, 2015;Sejjaaka & Kaawaase, 2014;Olsen, Sverdrup, Nesheim, & Kalleberg, 2016;Welsch & LaVan, 1981;Aranya & Ferris, 1984;Morrow & Wirth;1989;Aranya & Amernic, 1981;Reed, Kratchman, & Strawser, 1994;Ketchand & Strawser, 1998), nurses and hospital employees (e.g., Li, Early, Mahrer, Klaristenfeld, & Gold, 2014;Top, Akdere, & Tarcan, 2015;Fu & Deshpande, 2014;Yang, Liu, Chen, & Pan, 2014;Lisdiyono & Asyhar Assalmani, 2017;Laschinger, Nosko, Wilk, & Finegan, 2014;Nesje, 2015;Sharma & Dhar, 2016;Veličković et al, 2014;Yang, Liu, Huang, & Zhu, 2013;Blau, 1999;Mosadeghrad, Ferlie, & Rosenberg, 2008;Lum, Kervin, Clark, Reid, & Sirola, 1998;Ingersoll, Olsan, Drew-Cates, DeVinney, & Davies, 2002;Kuokkanen, Leino-Kilpi, & Katajisto, 2003;Lu, Lin, Wu, Hsieh, & Chang, 2002), lawyers (e.g., Wallace, 1995a;Lu, Liang, & Li, 2014), and teachers (Nart & Batur, 2014;Bogler & Somech, 2004). However, these studies only discussed the commitment of a particular professional job.…”
Section: Introductionmentioning
confidence: 99%